Association of Antiangiogenic Biomarker Soluble FMS-Like Tyrosine Kinase-1 (sFlt-1) with Preeclampsia - Mandeep Kaur; Sahiba Kukreja; Sangeeta Pahwa (Current Innovations in Medicine and Medical Science Vol. 9, 2022)
Preeclampsia (PE), a pregnancy induced hypertensive disorder remains one of the leading public health threat affecting approximately 8-10% of all pregnancies in developing countries. The etiology of preeclampsia is unknown but there is growing evidence that imbalance in the placental release of various angiogenesis regulatory factors to the maternal circulation is one of the significant contributor to its clinical manifestations. Various recent studies have highlighted the role of various serum angiogenic biomarkers like anti angiogenic regulatory factor sFlt-1(Soluble Fms like tyrosine kinase-1) and proangiogenic factor PLGF (Placental Growth factor) in screening, early prediction, diagnosis, and management of Preeclampsia. High circulatory levels of sFlt-1 are detectable several weeks before clinical presentation of preeclampsia. Aim: The purpose of this study was to determine association of serum levels of sFlt-1 with preeclampsia in second and third trimester of pregnancy. Study Design: Prospective cohort study Methods: The present study was conducted in a tertiary care hospital and study participants were divided into 2 groups: Normotensive and Preeclamptic. Participants were recruited during the second trimester. ELISA kits were used to test serum sFlt-1 concentrations in the second trimester (24-28 weeks) and the third trimester (after 28 weeks). ROC (Receiver operating characteristics) curve analysis was done for evaluation of AUC (area under curve), sensitivity and specificity using software defined cutoff values. Results: sFlt-1 levels in the preeclampsia group were considerably higher in the second and third trimesters as compared to the normotensive group, with medians of 313.07 versus 65.150 (p value<0.001) and 337.875 versus 76.925 (p value<0.001), respectively. The ROC curve analysis using 190.5 ng/ml as cut off point in second trimester showed sensitivity 90%, specificity 85%, AUC 0.832, 95%CI:(0.745-0.918) and in third trimester at cutoff point 271.5 ng/ml showed sensitivity 90%, specificity 90%, AUC 0.884, 95%CI:(0.817- 0.951). Conclusion: The biomarker sFlt-1 may help with preeclampsia prediction and early diagnosis. In the near future the clinical utility of these disease specific angiogenic biomarkers in early detection of preeclampsia might improve health outcomes by preventing adverse maternal and neonatal outcomes and serious complications.